Drug eluting balloons for resistant arteriovenous dialysis access stenosis. Issue 1 (March 2017) - Karnabatidis, Dimitrios; Kitrou, Panagiotis
Vascular access maintenance is vital for hemodialysis patients. Conventional balloon angioplasty is the gold standard of treatment in endovascular therapy according to published guidelines, accompanied by bare metal stents as a bail-out method. Several devices have been used so far with a view to improve patency outcomes, but only covered stents have been proposed as a valid alternative and only for venous juxta-anastomotic stenosis of arteriovenous grafts. Paclitaxel-coated balloons (PCBs) have been extensively investigated in the last few years in pilot studies with small numbers of patients in dialysis access. Results from these studies have been promising so far; however, a larger number of subjects is needed to prove outcomes. Aim of this analysis is to discuss current available studies and explore some critical aspects of PCB use in dialysis access treatment.